Differences in Learning Outcomes of Chemistry through Cooperative Learning Model Type Make a Match and Numbered Head Together on the Material of Electrolyte and Nonelectrolyte Solution of Students Class X in SMA Negeri 9 Palu - Nur Qamariya; Minarni R. Jura; Afadil Afadil (Jurnal Akademika Kimia, 2019)
Application of learning model is expected to build good communication between students with teachers and students with students in an effort to improve understanding of a concept. This study aimed to determine the differences in the learning outcomes of chemistry through cooperative learning model type make a match and numbered head together in the material of electrolyte and nonelectrolyte solution of students class X SMA Negeri 9 Palu. This type of research was pre-experimental with the static group pretest-posttest design. The sample used in this research was the students of class Xa (n = 23) as the first experiment 1 and students of class Xb (n = 23) as the second experiment 2 with. The result of data analysis obtained, the mean value of the experiment class 1 was 74.24 and in the experiment class 2 was 67.28. The result of hypothesis testing with t-test statistic on two side was obtained - ttable ≤ tcount ³ + ttable that was (-1.68 <3.27> +1.68 with significant level (α = 0.05) and degrees of freedom = 44. This indicates that H0 was rejected and Ha was accepted so that it can be concluded that there are differences in the students’ learning outcomes of chemistry through cooperative learning model type make a match and numbered head together in the material of electrolyte and nonelectrolyte solution of class X SMA Negeri 9 Palu.